Tombs and Necropoleis of Cyprus: A Corpus of the Hellenistic and Roman Burial Grounds - Vasiliki Lysandrou; Demetrios Michaelides; Athos Agapiou (Journal of Open Archaeology Data)
The dataset contains geospatial information relating to hundreds of single tombs and necropoleis across Cyprus, dating to the Hellenistic and Roman periods. The data were collected by the first author for the needs of her PhD thesis. The dataset is deposited on KTISIS and is hereby made available to future research efforts for update. There is substantial reuse potential pertaining to research on Cyprus as well as the wider Mediterranean in areas ranging from ancient topography and demography to funerary material culture and burial artefacts and customs.